DIGITAL INTEGRATION IN FOREIGN LANGUAGE EDUCATION - Feruza Atxamovna Shirinova (Bright Mind Publishing, 2026)
The fast advancement of digital technologies has profoundly reshaped foreign language education in the twenty-first century. Conventional instructional approaches are now increasingly supported by digital resources that enhance learner independence, engagement, and communicative ability. This thesis explores the significance of digital technologies in foreign language instruction by examining their theoretical foundations, practical implementation, and influence on educational outcomes. The research identifies both the advantages and limitations of digital integration and stresses the necessity of adopting a blended, learner-centered teaching model.
Keywords: Digital technologies, foreign language education, learner autonomy, blended learning, e-learning, communicative competence.